Improving History Learning Activities and Outcomes With the Project-Based Learning Model - Bolon, Merisa Kristin Tampu; Diansyah, Arfan; Megawati, Imelda (LPPPI Publishing, 2024)
The aim of this research is to apply a demonstrative learning approach to improve student activity and learning outcomes in history classes. Classroom action research is the research methodology used in this research. Class XI–5 students at SMA Negeri 14 Medan were used as research subjects. The findings of the second cycle learning evaluation, which involved 35 students, can be used to analyze this, there were 32 students who completed it or 88.88% of students achieved the specified KKM, namely 75. Compared to cycle I, only 23 students completed it or 63.88% or in the initial condition (pre-cycle) only 10 students completed it or 27.88%. The application of the demonstration method in history learning increases students' learning activities. Students will not only gain knowledge from the teacher, but with the demonstration learning method students can express their knowledge in the form of drama and role playing.